Essential Norms of Stević–Sharma Operators from General Banach Spaces into Zygmund-Type Spaces - M. A. Bakhit (Journal of Mathematics)
A Stević–Sharma operator denoted by Tψ1,ψ2,φ is a generalization product of multiplication, differentiation, and composition operators. Using several restrictive terms, we characterize an approximation of the essential norm of the Stević–Sharma operator Tψ1,ψ2,φ from a general class X of holomorphic function spaces into Zygmund-type spaces with some of the most convenient test functions on the open unit disk. As an application, we show that our results hold up for several other domain spaces of Tψ1,ψ2,φ, such as the Hardy space and the weighted Bergman space.